The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1186/1757-1626-2-212
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral fat embolism and the "starfield" pattern: a case report

Abstract: Nearly all long-bone fractures are accompanied by some form of fat embolism. The rare complication of clinically significant fat embolism syndrome, however, occurs in only 0.9-2.2% of cases. The clinical triad of fat embolism syndrome consists of respiratory distress, altered mental status, and petechial rash. Cerebral fat embolism causes the neurologic involvement seen in fat embolism syndrome. A 19-year-old African-American male was admitted with gunshot wounds to his right hand and right knee. He had diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 4 publications
2
21
1
Order By: Relevance
“…Most patients with CFE show complete neurological recovery despite initial cerebral dysfunction and prolonged coma. (6,8,14) This is also true in our patient, who was discharged from the hospital one month later without any neurological sequelae.…”
Section: Discussionsupporting
confidence: 77%
“…Most patients with CFE show complete neurological recovery despite initial cerebral dysfunction and prolonged coma. (6,8,14) This is also true in our patient, who was discharged from the hospital one month later without any neurological sequelae.…”
Section: Discussionsupporting
confidence: 77%
“…Characteristic findings on diffusion-weighted and susceptibility-weighted MR images provide valuable supporting evidence for the diagnosis of cerebral fat embolism syndrome. The starfield pattern, which consists of innumerable bright punc-tate foci of restricted diffusion against the dark background of brain parenchyma, has a limited differential diagnosis including diffuse axonal injury; cardiogenic, septic, or fat emboli; vasculitis; and minute hemorrhagic metastases (11)(12)(13)(14). In cerebral fat embolism syndrome, this pattern is thought to represent numerous sites of cytotoxic edema related to hemorrhage and infarction due to cerebral vessel occlusion by fat emboli.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of reported cases, patients with cerebral fat embolism due to trauma experienced neurologic changes that were transient and eventually followed by a full recovery (11)(12)(13)15). In patients with sickle cell disease, the clinical course of fat embolism is more often fulminant.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have reported that diffusion weighted cranial MRI is a useful adjunct in recognizing cerebral FES. [9][10][11] In our patient, cranial MRI was consistent with cerebral involvement. He had many scattered small lesions of limited diffusion within both cerebral hemispheres, basal ganglia, centrum semiovale and corpus callosum (Figure 1).…”
Section: Discussionmentioning
confidence: 81%